2021
DOI: 10.25077/ar.8.1.59-71.2021
|View full text |Cite
|
Sign up to set email alerts
|

Citing Others’ Works in Academic Texts: How Non-native Writers of English Across-disciplines Use Reporting Verbs and Reporting Signals in Their Research Article Introductions

Abstract: This study is aimed at investigating how Indonesian writers in multidiscipline use reporting verbs (henceforth RVs) and reporting signals (henceforth RSs) in their research article introductions in English. Fifty research articles (henceforth RAs) were chosen on purpose from the recent edition of five different English language journals in Multi-disciplines published in Indonesia (i.e., 10 from Applied Linguistics, 10 from Medicine, 10 from Animal Husbandry, 10 from Engineering and Technology, and 10 from Geog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 18 publications
0
4
1
Order By: Relevance
“…Regarding the differences, the results revealed that Indonesian authors of medium-ranking journals tended to use more argue verbs, find verbs, and show verbs than low-ranking journals in research article introductions in the field of English language teaching in terms of the frequency of the verb occurrences. These findings are in contrast to the study of Arsyad, Syahrial, & Hakim (2021) Another possible reason for the use of RVs such as argue verbs, find verbs, and show verbs is higher than in low-ranking ELT journals possibly caused by the number of citations or references used by them. The data show that the use of the integral citation is higher in medium-ranking ELT journals than in low-ranking ELT journals.…”
Section: Ranking Elt Journalscontrasting
confidence: 90%
See 1 more Smart Citation
“…Regarding the differences, the results revealed that Indonesian authors of medium-ranking journals tended to use more argue verbs, find verbs, and show verbs than low-ranking journals in research article introductions in the field of English language teaching in terms of the frequency of the verb occurrences. These findings are in contrast to the study of Arsyad, Syahrial, & Hakim (2021) Another possible reason for the use of RVs such as argue verbs, find verbs, and show verbs is higher than in low-ranking ELT journals possibly caused by the number of citations or references used by them. The data show that the use of the integral citation is higher in medium-ranking ELT journals than in low-ranking ELT journals.…”
Section: Ranking Elt Journalscontrasting
confidence: 90%
“…This study found that three types of reporting verbs were found in terms of communication, activity, and mental verbs. Further, in academic text, Arsyad, S., Syahrial., & Hakim, H. (2021) investigated the use of reporting verbs in the research article introductions written by Indonesian writers across disciplines. This study reported that the RVs in terms of "show", and "argue" groups were the most frequently found in the research article introduction, and tensed of RVs were often used in Present and Past Tense.…”
Section: Raningrum Arsyad Fadhli a Comparative Study On Reporting Ver...mentioning
confidence: 99%
“…The present perfect tense in RV can be employed to highlight the current state of affairs or convey a temporary conclusion from multiple works of literature (Swales & Feak, 2012). Arsyad et al (2021) argue that the limited use of the present perfect in EFL students' writing is due to their predilection for referring to a single study and research findings. It is in stark contrast to the citation practices by native English speakers or experts who prefer to cite generally accepted knowledge in the present tense and cite information from multiple sources collectively to indicate an area of inquiry with the present perfect.…”
Section: Tenses Of Rv In Efl Students' Academic Essaymentioning
confidence: 99%
“…However, studies have consistently reported that novice EFL writers have struggled with reporting verbs in their academic writing. It is the case for EFL writers in Indonesia (Amrullah et al, 2017;Arsyad et al, 2021), Iran (Yeganeh & Boghayeri, 2015), Malaysia (Manan & Noor, 2014), Thailand (Jaroongkhongdach, 2015;Jogthong, 2001), Vietnam (Loan & Pramoolsook, 2015), Czech (Jarkovská & Kučírková, 2020), Spain (Luzón, 2018;Soler Monreal & Gil Salom, 2011), Ghana (Agbaglo, 2017), and China (Kwon et al, 2018;Wen & Pramoolsook, 2021). The studies have found a predilection for EFL writers to use RV in a limited manner, especially in research acts (such as find, show, analyze) and discourse factive Volume 13, Number 2, September 2022, 210-230 (such as explain, argue, affirm).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation